2016
DOI: 10.1016/j.ijid.2016.11.222
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study to assess visceral leishmaniasis in Armenia, 2015

Abstract: determine associations between the preferred feeding choices and the factors affecting the decisions.Results: The findings revealed good knowledge (60%) of the infant feeding options among the respondents. About 42.9% of the women felt the counsellors were not convinced to certain limit which method was best, hence they not confidently guide them on the correct options. The adoption of infant feeding options as recommended by WHO was not optimal. Reasons included deterrents like financial limitations in 36.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…First seroepidemiological studies conducted 2015 and 2016 in active Armenian VL foci (Yerevan, Armavir, Ararat, Lori, Tavush, Syunik) indicated that the seroprevalence in the ~1200 tested children under 10 years was rather low (0.3%). In addition, seroprevalence in dogs was between 3 and 16%, with the highest percentages in Tavush (16.1%), Syunik (9.3%) and Lori (6.5%), stressing the potential of dogs as reservoir in these VL foci (Paronyan et al ., 2017). Concerning bordering countries, such as Georgia, natural Leishmania foci are restricted mainly to the Eastern part of the country, some of them bordering to the north of Armenia (Lori and Tavush districts).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First seroepidemiological studies conducted 2015 and 2016 in active Armenian VL foci (Yerevan, Armavir, Ararat, Lori, Tavush, Syunik) indicated that the seroprevalence in the ~1200 tested children under 10 years was rather low (0.3%). In addition, seroprevalence in dogs was between 3 and 16%, with the highest percentages in Tavush (16.1%), Syunik (9.3%) and Lori (6.5%), stressing the potential of dogs as reservoir in these VL foci (Paronyan et al ., 2017). Concerning bordering countries, such as Georgia, natural Leishmania foci are restricted mainly to the Eastern part of the country, some of them bordering to the north of Armenia (Lori and Tavush districts).…”
Section: Discussionmentioning
confidence: 99%
“…In 1999, after a long period without any notification, a VL case was diagnosed in a 4-years-old child from the village Shnogh in the Lori district. Between 1999 and 2016, 116 indigenous and 99 imported cases of VL were recorded in the country mainly in the districts Syunik, Tavush, Lori and Yerevan (Paronyan et al ., 2015; Sukiasyan et al ., 2017) (Fig. 1), some of them were included in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The first sero-epidemiological studies performed in active Armenian VL foci (Yerevan, Armavir, Ararat, Lori, Tavush, and Syunik) in 2015 and 2016 revealed that the seroprevalence in the ∼1200 studied children under the age of ten years was relatively low (0.3 percent). Furthermore, seroprevalence in dogs ranged from 3 to 16 percent, with the highest percentages in Tavush (16.1 percent), Syunik (9.3%), and Lori (6.5 percent), highlighting the importance of dogs as a reservoir in these VL foci [9].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of VL in Armenia is 0.03-0.6 per 100,000 people, the highest among children up to 3 years old [ 5 ]. The signs and symptoms of VL are fever, weight loss, failure to thrive, and hepatosplenomegaly.…”
Section: Introductionmentioning
confidence: 99%